Biostratigraphical and sequence correlation of the Cenomanian successions in Mangyshlak (W. Kazakhstan) and Crimea (Ukraine) with those in southern England - Gale, A; Hancock, J; Kennedy, W (1999)
Cenomanian successions in southern England (UK), Crimea (Ukraine) and Mangyshlak (Western Kazakhstan) are briefly described and the evidence for biostratigraphical correlation, based on ammonites and inoceramid bivalves is reviewed in the light of new discoveries. Our conclusions differ significantly from those of previous authors in that: i) we date the base of the Cenomanian in Crimea as early M. dixoni Zone age, rather than M. mantelli Zone age, and ii) most of the supposed Middle Cenomanian in Mangyshlak is more correctly placed within the Lower Cenomanian M. dixoni Zone. Sedimentological evidence from the Crimea and Mangyshlak is used to construct a sequence stratigraphical interpretation for each of these regions. The sequences thus identified are correlated by ammonite and inoceramid biostratigraphy with those described previously (1-6) from the Anglo-Paris Basin. The Crimean succession is very similar in both facies development and the distribution and extent of hiatuses to the marly chalk succession of the northern Anglo-Paris Basin, and sequences 3-6 are identified. In the shallower water sandy and marly successions in Mangyshlak sequences 1, 2, 3, 5 and 6 are identified. 4 is missing within a major hiatus which extends across Mangyshlak.